Understanding Education of Authoritative Islamic Law Perspective Khaled Abou el Fadl - Mahfud, Choirul (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
Problems with Gender-biased Islamic law education and authoritarianism in the United States have invited the anxiety of prominent Muslim intellectual, Khaled Abou El Fadl. In his book on the Speaking in God's Name, Khaled revealed a crucial hermeneutic problem related to the relation of text (text), author (reader). Khaled also revealed the problem of abuse of